2014
DOI: 10.1097/sih.0000000000000030
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and 1-Year Chest Compression Quality

Abstract: Instantaneous audiovisual feedback training on CC quality produces immediate improvements in compression rate, hand placement, as well as depth and recoil compliance. These improvements, however, are not retained 1 year later. Improved depth performance may be correlated to an increased training frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The targeted instruction and use of feedback could have a positive influence on the depth. In the case of feedback devices, several studies had reported that the quality of chest compressions was improved, 3,4,6,18,19 although the quality of resuscitation may vary depending of feedback device used. 20 The quality of rescue breaths was very poor in all three groups with reference to pre-test and post-test.…”
Section: Discussionmentioning
confidence: 99%
“…The targeted instruction and use of feedback could have a positive influence on the depth. In the case of feedback devices, several studies had reported that the quality of chest compressions was improved, 3,4,6,18,19 although the quality of resuscitation may vary depending of feedback device used. 20 The quality of rescue breaths was very poor in all three groups with reference to pre-test and post-test.…”
Section: Discussionmentioning
confidence: 99%
“…lww.com/SIH/A747). 46,67,74,77,79,[81][82][83]86,89,92,93,96,105,109,138,139 Most studies were on BLS training and generally showed a significant benefit of objective and real-time feedback from feedback devices when compared with no feedback (from device or instructor) or instructor-feedback only (without a feedback device). 67,74,92 Most studies assessed CPR quality immediately after training, but 1 study suggested that real-time audiovisual feedback may improve skill retention at 3 months.…”
Section: Feedback Devicesmentioning
confidence: 99%
“…The first 331 reported no difference in CPR performance between a group of laypeople trained with a CPR feedback device compared with a control group at 1 year after training. In the second study of CPR training of healthcare providers, 319 both control and feedback groups improved from baseline at 1 year after training, but there was no difference between the control and feedback groups.…”
Section: Consensus On Sciencementioning
confidence: 92%
“…325 Five studies showed improvement in CPR skills at the end of training with the use of feedback devices compared with no feedback device. 319,320,323,328,330 Two studies showed no difference in performance. 322,326 One study showed worse CPR performance at the conclusion of training, although this study has a high risk of bias because of unclear outcome definitions and the use of the audiovisual feedback system to replace an instructor.…”
Section: Cpr Performance From Training Conclusion To 1 Year Aftermentioning
confidence: 98%